2012
DOI: 10.1111/bjc.12008
|View full text |Cite
|
Sign up to set email alerts
|

The mental health, emotional literacy, cognitive ability, literacy attainment and ‘resilience’ of ‘looked after children’: A multidimensional, multiple‐rater population based study

Abstract: In general terms, this study supports the findings of previous research studies. However, evidence of positive exceptions across and within all domains cautions against overgeneralization of findings. The findings also implicate parental contact and mainstream education in the promotion of resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
0
25
1
3
Order By: Relevance
“…Their journey from childhood to adulthood is characterized not only by the social expectations of all young people as they mature but also by services changing as they turn 18 (McDonagh & Viner ; Stein ). Health outcomes for this group on average are poor in comparison with the wider population (Botchway et al ; Rees ; Stein & Dumaret ). Some of those transferring out of paediatric into adult healthcare services will transfer across more than one specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Their journey from childhood to adulthood is characterized not only by the social expectations of all young people as they mature but also by services changing as they turn 18 (McDonagh & Viner ; Stein ). Health outcomes for this group on average are poor in comparison with the wider population (Botchway et al ; Rees ; Stein & Dumaret ). Some of those transferring out of paediatric into adult healthcare services will transfer across more than one specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Решение этой задачи требует комплексного изучения развития мозга с учетом взаимовлияния когнитивного потенциала, эмоционально-личностных характеристик, социального окружения и социального результата [1]. Комплексная оценка состояния психики детского населения необходима для определения групп риска когнитивно и академически неуспешных детей, профилактики негативных динамических изменений в их социализации с целью позитивных изменений их социальной жизнедеятельности [2][3][4].…”
Section: обоснованиеunclassified
“…In recent years there has been growing recognition that, compared with children not looked after but with similar socioeconomic backgrounds, LACs are at increased risk of a range of adverse outcomes in adulthood, including educational underachievement; 132 139 In their follow-up analysis of the 1970 British cohort study and controlling for other causes of disadvantage, Viner and Taylor 140 found that a history of being in care as a child could be linked with lower social status as an adult and more problems such as mental and physical health problems and homelessness. There were also sex-specific associations; women who had experienced care were more likely in their teens to have been excluded from school, whereas men with a care history were more likely to be unemployed.…”
Section: Introductionmentioning
confidence: 99%
“…Rees 132 reported the findings of a multidimensional, multiple-rater, population-based study of all LACs aged 7-15 years accommodated by one local authority (n = 193). The study aimed to overcome some of the limitations associated with earlier studies, such as small sample sizes and high attrition; restricted access to LACs; a focus on small, purposive samples; and reliance on case file audits.…”
Section: Introductionmentioning
confidence: 99%